Effects of Boron Nitride Coatings at High Temperatures and Electromagnetic Wave Absorption Properties of Carbon Fiber-Based Magnetic Materials. (20th January 2020) - Sun, Qilong; Ye, Wei; Cheng, Jiahao; Long, Xiaoyun
Abstract : An electromagnetic (EM) wave-absorbing material with a three-layer structure is prepared by depositing magnetic particles and a high-temperature resistant coating on the surface of the carbon fiber (CF) with in situ hybridization. Accordingly, the structure, chemical composition, morphology, high-temperature resistance, EM characteristics, and EM wave absorption of the composite materials were analyzed. The composite materials contained CFs, and the magnetic particles, such as Fe3 O4, NiFe2 O4, CoFe2 O4, and Ni3 Fe, distributed along the axial direction of the fiber, while boron nitride (BN) existed in the outermost coating layer. This preparation method improves the oxidation resistance and EM wave absorption performance of the CF. When the concentrations of the metal salt solution and the original BN solution are 0.625 × 1.5  mol L -1 [n FeC l 3 : n CoS O 4 : n NiS O 4 = 2 : 2 : 1 ] and 4 mol L -1 [n H 3 B O 3 : n CO N H 2 2 = 1 : 3 ], respectively, the thermal decomposition temperature of the prepared CF/1.5FeCoNi/2BN is increased from 450°C to 754°C. In the frequency range of 10.6–26 GHz, the EM wave loss is less than −10 dB (the bandwidth spans 15.4 GHz). The CF-based composite material prepared in this study has the characteristics of light weight, wide absorption band, and strong oxidation resistance and constitutes the reference basis for the study of other high-temperature, EM wave-absorbing materials.